2022
DOI: 10.1108/emjb-12-2021-0200
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 full vaccination and blockchain size: empirical evidence from the cryptocurrency market

Abstract: PurposeThis paper aims to analyse COVID-19 indices and blockchain features on Bitcoin and Ethereum returns, respectively. The authors focus on the most used and owned cryptocurrencies that cover Europe, the US and Asian countries.Design/methodology/approachAn autoregressive distributed lag panel (pooled mean group and mean group) is utilized, and a robustness check is incorporated by using a Random Effect Model and Generalized Method of Moments (GMM).FindingsFour new findings were discovered, including (1) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 61 publications
0
0
0
Order By: Relevance
“…We used the robust option in our diff-GMM model. Utilizing GMM as a robustness check was also done (Aiello & Cardamone, 2005;Havidz et al, 2021Havidz et al, , 2022Vo et al, 2022). The model relies on minimal assumptions and provides precise, consistent estimates even in panels with few time-series observations per individual model (Moral-Benito et al, 2019;Wooldridge, 2001).…”
Section: Generalized Methods Of Moments (Gmm) Model For Robustness An...mentioning
confidence: 99%
See 1 more Smart Citation
“…We used the robust option in our diff-GMM model. Utilizing GMM as a robustness check was also done (Aiello & Cardamone, 2005;Havidz et al, 2021Havidz et al, , 2022Vo et al, 2022). The model relies on minimal assumptions and provides precise, consistent estimates even in panels with few time-series observations per individual model (Moral-Benito et al, 2019;Wooldridge, 2001).…”
Section: Generalized Methods Of Moments (Gmm) Model For Robustness An...mentioning
confidence: 99%
“…Hence, we used 'vaccine dose' as the new keyword to provide a different perspective and stress on the dose, instead of merely the vaccine. Recent research by Havidz et al (2022) constructed a vaccine confidence index against COVID-19 relying on the primary vaccination series (Dose 1 and Dose 2). The results revealed that the vaccine confidence index (VCI) pushed economic recovery and increased demand for the Bitcoin market.…”
Section: Introductionmentioning
confidence: 99%